Apigenin Alleviates Liver Fibrosis by Inhibiting Hepatic Stellate Cell Activation and Autophagy via TGF-β1/Smad3 and p38/PPARα Pathways - Jie Ji; Qiang Yu; Weiqi Dai; Liwei Wu; Jiao Feng; Yuanyuan Zheng; Yan Li; Chuanyong Guo (PPAR Research)
Objective. The aim of this study is to confirm the hepatocellular protective functions of apigenin and the molecular mechanism on liver fibrosis in mice. Methods. Carbon tetrachloride (CCl4) and bile duct ligature (BDL) mouse fibrosis models were used to investigate the effects of apigenin on liver fibrosis. Sixty-six male C57 mice were randomly divided into eight groups, including the vehicle group, CCl4 group, CCl4+L-apigenin (20 mg/kg) group, CCl4+H-apigenin (40 mg/kg) group, sham group, BDL group, BDL+L-apigenin(20 mg/kg) group, and BDL+H-apigenin(40 mg/kg) group. Serum liver enzymes (ALT and AST), proteins associated with autophagy, and indicators linked with the TGF-β1/Smad3 and p38/PPARα pathways were detected using qRT-PCR, immunohistochemical staining, and western blotting. Results. Our findings confirmed that apigenin could decrease the levels of ALT and AST, suppress the generation of ECM, inhibit the activation of HSCs, regulate the balance of MMP2 and TIMP1, reduce the expression of autophagy-linked protein, and restrain the TGF-β1/Smad3 and p38/PPARα pathways. Conclusion. Apigenin could alleviate liver fibrosis by inhibiting hepatic stellate cell activation and autophagy via TGF-β1/Smad3 and p38/PPARα pathways.